Advances in Dynamic Games Applications to Economics, Finance, Optimization, and Stochastic Control - Nowak, Andrzej S.; Szajowski, Krzysztof (Annals of the International Society of Dynamic Games, 2005)
This book focuses on various aspects of dynamic game theory, presenting state-of-the-art research and serving as a guide to the vitality and growth of the field and its applications. The selected chapters, written by experts in their respective disciplines, are an outgrowth of presentations originally given at the 9th International Symposium of Dynamic Games and Applications. Featured throughout are useful tools for researchers and practitioners who use game theory for modeling in many disciplines. Major topics covered include: * repeated and stochastic games * differential dynamic games * optimal stopping games * applications of dynamic games to economics, finance, and queuing theory * numerical methods and algorithms for solving dynamic games * Parrondo's games and related topics A valuable reference for practitioners and researchers in dynamic game theory, the book and its diverse applications will also benefit researchers and graduate students in applied mathematics, economics, engineering, systems and control, and environmental science.